Factors influencing exclusive breastfeeding practices in rural areas in south Benin - Kossou, Jahdiel; AMOUSSA HOUNKPATIN, WALIOU BODOURIN AYANDA; LOKONON, Jaurès H. F.; Hounyo, Clarisse; FLENON, Aubierge Joelle; Goudjo, frejus; Lachgue, Sara Ait; BENKIRANE, Hasnae; El Kari, Khalid; Aguenaou, Hassan (My University, 2021)
This study is part of the national programme for the promotion of exclusive breastfeeding (EBF) and was technically supported by the International Atomic Energy Agency. It aimed to determine the factors leading to the cessation of EBF among mothers living in areas benefiting from an important breastfeeding promotion actions in southern Benin. The practice of EBF was measured using “deuterium oxide dose to the mother” technique in 105 mothers during 6 month’s post-partum. Factors influencing the duration of this practice were investigated through an individual interview with the mothers and their relatives. The prevalence of EBF practice in lactating mothers was 58.7%, 29.1%, and 2.4% at 1, 3, and 6 months postpartum respectively. The main factor favoring this practice at 1 and 3 months was sufficient breastmilk supply. Continuation up to 6 months was due to the support of the family and belief in its benefits. On the other hand, the principal factors that led to its interruption at 1 and 3 months were insufficient breastmilk production and the giving of herbal teas and water to the babies. After 6 months, the drastic drop of EBF was due to the lack of the support from fathers. Integrating these factors into EBF promotion actions might increase practice.
Keywords: Exclusive breastfeeding practice; factors influencing; Benin